2004
DOI: 10.1002/bsl.597
|View full text |Cite
|
Sign up to set email alerts
|

Women with co‐occurring substance use and mental disorders (COD) in the criminal justice system: a research review

Abstract: Associated with the dramatic increase in the numbers of women entering the criminal justice system is the recognition of the prominent role of co-occurring substance use and mental disorders (COD) in the lives of female offenders. This article reviews current research examining the prevalence and range of COD among female offenders, the variety of psychosocial problems faced by the female offender with COD, and the multiple treatment needs of women with COD who are under criminal justice supervision. Women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 80 publications
5
76
0
Order By: Relevance
“…The patterns of co-occurring disorders among women in criminal justice systems are similar to, but more severe than, those found for women in community-based treatment studies (Sacks, 2004). Female inmates, compared with women in community epidemiologic studies, have elevated rates of substance use and mental health disorders, including substance abuse and dependence, mood disorders, borderline personality, and PTSD (Jordan, Schlenger, Fairbank, & Caddell, 1996;Maden, Swinton, & Gunn, 1994;Teplin, Abram, & McClelland, 1996).…”
Section: Female Offenders With Co-occurring Disordersmentioning
confidence: 94%
“…The patterns of co-occurring disorders among women in criminal justice systems are similar to, but more severe than, those found for women in community-based treatment studies (Sacks, 2004). Female inmates, compared with women in community epidemiologic studies, have elevated rates of substance use and mental health disorders, including substance abuse and dependence, mood disorders, borderline personality, and PTSD (Jordan, Schlenger, Fairbank, & Caddell, 1996;Maden, Swinton, & Gunn, 1994;Teplin, Abram, & McClelland, 1996).…”
Section: Female Offenders With Co-occurring Disordersmentioning
confidence: 94%
“…Findings about the Rowan-Szal et al, 2000), and multiple community treatment modalities (Compton et al, 2000). Co-occurring disorders of substance abuse and mental health also are common and consistently noted among females in the criminal justice system (Messina et al, 2006;Pelissier et al, 2003;Peters et al, 1997;Sacks, 2004;Sheridan, 1996). Considering these studies, we expected that a strong correlation between mental health issues and community treatment utilization among female participants in the current study.…”
mentioning
confidence: 94%
“…Studies have shown that substance-abusing women report increased mental health issues-especially, depression and anxiety-when compared to men (Brady, Grice, Dustan, & Randall, 1993;Gray & Saum, 2005;Rowan-Szal et al, 2000;Sacks, 2004). In addition, female community treatment participants report higher rates of mood disorders, phobias, panic disorder, and obsessivecompulsive disorder, when compared to men (Compton et al, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, substance abuse and trauma-related mental health problems frequently cooccur among incarcerated women (Battle, Zlotnick, Najavits, Gutierrez, & Winsor, 2003;Najavits, Sullivan, Schmitz, Weiss, & Lee, 2004;Sacks, 2004;Staton, Leukefeld, & Webster, 2003).…”
mentioning
confidence: 98%